KKM Refungsionalisasi Masjid: Optimalisasi Fungsi dan Peran Masjid Al-Ikhlas Dusun Glundengan Desa Suci Kecamatan Panti Kabupaten Jember - Finadatul Wahidah; Abdul Sholeh; Putri Nur Hayati (Universitas Nurul Jadid, 2020)
This community service is to optimize the position and function of the mosque as not merely a location for worship rituals, but also a place of education, such as religious education (Madrasah Diniyah), tutoring (Bimbingan Belajar), Al-Quran education park (Taman Pendidikan Al-Quran). Since some of the Suci people at the Glundengan village are very busy with work and other activities, they have lack of attention on their religious affairs. By announcing the five prayer at the Al-Ikhlash Mosque, this community service which is based on PAR (Participatory Action Research) approach as a methodological approach is to arouse the community's enthusiasm to pray in the Mosque, and we provide an example to enliven the congregation at the mosque. The most of Glundengan people have lower educational level, which can be seen from the lack of undergraduate graduates, and this situation has caused any migration to town. The program of ‘refunctionalizing’ mosque is important, since there is also Christian religious worship in Glundengan, a church located in RT 2, which is not far from the mosque.